SoTL in Latin America: Bridging Cultures, Transforming Teaching and Learning - Oscar Jerez Yañez; Jorge Maldonado Mahauad; Gisela Schwartzman; Carolina Rodriguez Enríquez; Sugey Montoya Sandí; Álvaro Herrera Alcaíno; Cristina Del Mastro Vecchione; Miguel Morales-Chan; Wendy Díaz Pérez; Ivory Mogollón de Lugo; Gina Camargo De Luque; Alejandra Martínez Barrientos; et al. (Teaching & Learning Inquiry: The ISSOTL Journal)
ABSTRACT